Simulation and Techno-Economic Analysis of On-Grid Battery Energy Storage Systems in Indonesia - Agus Ramelan; Feri Adriyanto; Chico Hermanu Brillianto Apribowo; Muhammad Hamka Ibrahim; Irwan Iftadi; Gilang Satria Ajie (Journal of Electrical, Electronic, Information, and Communication Technology, 2021)
The limited capacity of renewable energy sources in the grid utility is a challenge. Increasing the capacity of renewable energy sources is supported by energy storage in the grid. The Battery Energy Storage System (BESS) allows storing more electricity from New and Renewable Energy (EBT) sources to meet load requirements. This paper designs a techno-economic study of various battery technologies using HOMER (Hybrid Optimization Modeling Software) software simulation. Simulations are made for grid-connected photovoltaic systems in Indonesia. HOMER is used to find the energy cost ($ / kWh) for each type of battery technology and battery system size. The simulation is designed using 1MWp PV component parameters, inverter, energy storage to be compared, residental load, and connected to the grid. The results will help to determine which technology and battery size is more suitable for the system. The findings from this paper resulted in the lowest Levelized Cost Of Energy (LCOE) of $ 1.03 in solar power generation.